PENDEKATAN HUMANISTIK PIMPINAN TERHADAP PENERIMA MANFAAT PANTI PELAYANAN SOSIAL LANJUT USIA SUDAGARAN BANYUMAS - Farros Fauzul Haq; Muh Hikamudin Suyuti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines how the principles of Abraham Maslow's humanistic theory are applied in the leadership style at the Sudagaran Social Service Center for the Elderly (PPSLU), Banyumas. Using qualitative research methods, which include interviews and direct observation, this study aims to understand the extent to which the approach used by the leadership reflects humanistic values, especially in meeting the level of basic human needs. The results showed that the leadership of PPSLU Sudagaran consistently adopted an individual-centered approach, giving equal attention to the physical and psychological needs of the elderly. Daily interactions in the form of empathy, focus, support and active involvement of leaders in the activities of the elderly demonstrate a deep understanding of their needs, in line with Maslow's theory. The study concludes that leadership based on humanistic principles has a significant positive impact on older people's well-being, creates a supportive service environment and encourages the implementation of similar models in other social care homes, and inspires further research to identify best practices in older people's services.